Investigation of flow field characteristics around a novel high-efficiency tandem dual-rotor wind turbine under different rotor spacings - Xinkai Li; Xinkai Li; Xiaojiang Guo; Xiaojiang Guo; Caicai Liao; Caicai Liao; Zhaoliang Ye; Zhaoliang Ye; Xin Shen (Frontiers in Energy Research)
IntroductionTandem dual-rotor wind turbines achieve efficient wind energy capture through aerodynamic coupling between upstream and downstream rotors. However, the influence mechanism of rotor spacing on complex flow fields and turbine performance remains unclear.MethodsAiming at this problem, a high-precision computational fluid dynamics (CFD) method was adopted to construct a physical model of dual-rotors with real blade geometry. Using global structural grid meshing and the Transition-SST turbulence model, the flow characteristics of air around the rotors were systematically investigated under six typical spacings ranging from 0.2 D to 2.0 D (D is the diameter of the front rotor).Results and discussionThe study found that as the spacing increases, the power of the front rotor increases logarithmically, while the power of the rear rotor gradually decreases. The total power of the dual-rotors continues to rise, showing different growth rates before and after 0.5 D. Flow field analysis indicates that the wake blockage effect of the front rotor on the rear rotor is significant at small spacings, while the wake velocity recovers more fully and the turbulence mixing effect enhances at large spacings. This research reveals the regulation law of rotor spacing on aerodynamic interference effects, provides key parameter basis for optimizing wind energy capture and designing structural loads of dual-rotor turbines, and fills the research gap on the influence of tandem dual-rotor spacing on flow field characteristics.